Histopathological Findings of Liver Autopsy Cases: Study at a Tertiary Care Hospital - Hossain, A B M Iftekhar; Karim, Syeda Noorjahan; Biswas, Prasun; Bintay Eunus, Momtaz Ferdousi; Rawnuck, Tanzila; Sharmin, Rayhana; Saleh, A F M (Mediscope, 2025)
Background and objective: Liver diseases are common health problems throughout the world. Most of the chronic liver diseases, even in advanced stages, may cause no prominent clinical signs or symptoms. They either go undiagnosed or are found incidentally during general health check-ups, investigations for other diseases, surgery, or autopsy. This study will provide important information about the frequency of undiagnosed chronic hepatic lesions in autopsy specimens in this area and incidental autopsy findings can contribute to discovering many of the common liver diseases which will provide a framework for the clinician to pursue further diagnostic studies. Methods: This descriptive cross-sectional study was conducted at the Department of Pathology, Mymensingh Medical College (MMC) from March 2017 to December 2018. The specimens were from medicolegal autopsies, as clinical autopsies are not done in Bangladesh. The autopsy cases that fulfilled the selection criteria were enrolled as the study samples. After the exclusion of decomposed and extensive necrosed samples, 171 cases were included in the study. After routine tissue processing, all slides were stained with Hematoxylin & Eosin (H/E) stains. A special stain with Masson’s trichrome was done to evaluate the liver architecture and pattern of fibrosis, whenever necessary. After that histopathological evaluation was done and diagnosis was made. The data was tabulated and statistical analysis was performed. Results: Out of 171 cases, 151 cases had normal histological findings and only 11.7% had pathological findings. Of them, the most common changes were steatosis, which was in twelve (7%), chronic hepatitis in four (2.3%) and congestion in three (1.8%) cases. Secondary malignancy was found in one (0.6%) case. The most common lesion observed in the 5th decade was steatosis. While chronic hepatitis was not observed before the age of 30 years. It was seen in equal distribution in the 4th decade and the 5th decade. One case of congestion was seen in the 4th decade while two cases were observed in the 5th decade. Also, one case of secondary malignancy was seen in the 5th decade. Conclusion: The study result will be beneficial for the medical community by providing information regarding the reliable frequency of hepatic disease in this region of our country. Mediscope 2025;12(1): 10-17